2013
DOI: 10.1016/j.actatropica.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Lutzomyia longipalpis in an area of visceral leishmaniasis transmission in north-eastern Brazil

Abstract: Visceral leishmaniasis is a major public health issue in South America, where the disease is rapidly spreading. Changes in ecology and distribution of the principal vector, Lutzomyia longipalpis are among the factors accounting for the increasing incidence of the disease in this region. However, information about the ecology of L. longipalpis is still incipient, which may directly impair the implementation of effective control programs. Herein, the ecology of L. longipalpis was studied in a focus of visceral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 30 publications
2
30
0
5
Order By: Relevance
“…However, population dynamics of sand flies may vary from region to region, as well as with climatic variables (20) (21) . In this study, and others (22) (23) (24) (25) , the highest sand fly frequency and diversity occurred during the rainy season.…”
Section: Gender (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, population dynamics of sand flies may vary from region to region, as well as with climatic variables (20) (21) . In this study, and others (22) (23) (24) (25) , the highest sand fly frequency and diversity occurred during the rainy season.…”
Section: Gender (%)mentioning
confidence: 99%
“…neighborhoods located in a completely urbanized area, considered as old neighborhoods (sites 13-18); and IV. APPs (sites [19][20][21][22][23][24] (Figure 1).…”
Section: Sand Fly Collection and Identificationmentioning
confidence: 99%
“…This species was collected in large numbers from chicken coops, pigsties, and corrals. In fact, it is known that chickens are among the preferred hosts for the blood meal of L. longipalpis (20) (26) .…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal dynamics of sandfl ies can vary greatly from region to region, and the varying climatic factors, over time, might cause species to have different patterns in the same geographical area (5) (26) . The specimens collected in this study showed abundance in the months of May and July 2015, corresponding to the months before and after the wettest period of the year.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that climatic and other factors (such as the presence of vegetation) have an influence on the incidence of phlebotomines (COSTA et al, 2013). In addition, some species may present different seasonal patterns in the same geographic area, due to climatic variations (GUIMARÃES et al, 2012).…”
Section: Discussionmentioning
confidence: 99%